Back Cover: (S)‐BINOL Immobilized onto Multiwalled Carbon Nanotubes through Covalent Linkage: A New Approach for Hybrid Nanomaterials Characterization (ChemNanoMat 3/2015). Issue 3 (July 2015) - Monteiro, Carlos J. P.; Carabineiro, Sónia A. C.; Lauterbach, Tobias; Hubbert, Christoph; Hashmi, A. Stephen K.; Figueiredo, José L.; Pereira, Mariette M.
Abstract : Nanohybrids . "Bee"nol on "beehives": In this collaborative work between the Portuguese Universities of Coimbra and Porto, and the German University of Heidelberg, BINOL [(S)‐6‐(4‐(methoxycarbonyl)phenyl)‐1, 1′‐bis‐2‐naphthol] derivatives were immobilized on multiwalled carbon nanotubes and used in diethyl zinc and titanium isopropoxide catalyzed alkylation of benzaldehyde. These results open a plethora of applications for this new kind of immobilized hybrid materials. For more information, see the Full Paper onpage 178 by Sónia A. C. Carabineiro, Mariette M. Pereira, and co‐workers, which is featured on the back cover.